Carcass Characteristics of Broilers Fed Sugarcane Press Residue with Biotechnological Agents - Suresh, B.N.; Reddy, B.S.V.; B.H., Manjunatha Prabhu; Jaishankar, N. (International Journal of Poultry Science, 2009)
An experiment was carried out to study the effect of inclusion of sun-dried Sugarcane Press Residue (SPR) as a feed ingredient with some biotechnological interventions on the carcass characteristics and gut development of broilers. Experimental diets were prepared by incorporating SPR at 0, 5 and 10 per cent and further such diets were supplemented with or without lipid utilizing agents (lipase and lecithin) or NSP degrading enzymes or together to result in a set of 12 diets. Each diet prepared for starter (0-14 days), grower (15-28 days) and finisher (29-42 days) phases was offered to triplicate groups of 10 broiler chicks each. At the termination of the experiment (42nd day), no significant (p>0.05) differences in dressing percentage, meat to bone ratio, abdominal fat and relative weights of different organs viz., liver, heart, gizzard, proventriculus and spleen excepting bursa (p